THE SYSTEM OF EVALUATION MODELS UI WEB APPLICATION - Anna A. Pupykina; Anna E. Satunina (Статистика и экономика)
Graph theory provides a means for a formalized description of the model of interaction and ensure the provision of precisemathematical relationships between thecomponents. A scheme for modeling Web applications was proposed. The system of evaluation models UI Web application. Taking into account such factors as understandability, predictability, learning. For each indicator matrix is constructed for assignment to class compliance.